IMPLEMENTASI NILAI-NILAI PENDIDIKAN AKHLAK DALAM PERSPEKTIF AL-QUR’AN DAN RELEVANSINYA DENGAN UU SISDIKNAS NO 20 TAHUN 2003 - Zaenal Arifin (el-Moona: Jurnal Ilmu Pendidikan Islam, 2021)
The aims of this study are: (1) to find out the verses that contain the educational values ​​of Surah al 'Alaq; 96: (1-5), (2) for the formation of morals contained in Surah QS. al Ahzab verse 21, (3) to emphasize that the Prophet Muhammad SAW has the best and most noble qualities of Surah Al Qalam; (68:4). Based on the results of this study, the researchers obtained that moral education in Surah al 'Alaq; 96: (1-5) This verse contains wisdom that can be used as a provision for life while in the world so relevant to the National Education System Law No. 20 of 2003. Morals is one of the interesting discussions and continues to be a study for Muslims because the key to goodness is values ​​in life in the world and is the beauty of worship. In the context of national education in Indonesia, morality is the basis for the formation of the personality and goals of educators.